Eating disorders in elite synchronized swimmers - Adao Perini, T.; Silva Vieira, R.; dos Santos Vigario, P.; Lameira de Oliveira, G.; dos Santos Ornellas, J.; Palha de Oliveira, F. (Revista Brasileira de Medicina do Esporte, 2009)
The aim of the present study was to identify the Eating Behavior Disorder (EBD) or precursory syndromes and the level of distortion of the body image of elite synchronized swimming athletes. This sport modality is considered of risk for development of eating disorders for valuing, among other aspects, the softness and beauty of movements, which, partly, are associated to low body mass. METHODS: Twenty-seven synchronized swimmers, grouped as Junior (15.6 ± 0.8 years) or 08 as senior category (19.0 ± 1.3 years) were studied. A group of 32 non-athletes adolescents (15.0 ± 1.6 years) was used for comparison with the athletes. For the analysis Three instruments were used in accordance with the objective of the evaluation: 1- Eat-26-presence of inadequate eating behaviors; 2-BITE-presence of suggestive attitudes of Bulimia and 3-BSQ-dissatisfaction of body self-image. RESULTS: The athletes and the non-athletes presented compatible anthropometrical parameters with healthy standards for age and sex; however, there is evidence of body image dissatisfaction associated with pathological control of body weight. CONCLUSIONS: The results found in the present study portray a worldwide trend of concern with the appearance among adolescents which is capable of leading them to the adoption of unhealthy behaviors.